The employment of documentary film in enhancing Arabic writing skills among non-native speakers from the experts’ perspective - Tengku Abdul Rahman, Tengku Ainul Farhah; Chik, Abdul Rahman; Sahrir, Muhammad Sabri (David Publishing Company, 2016)
Nowadays, having access to authentic material for language learning, such as documentary film programs is very easy for all students and teachers around the world. The importance of this comprehensive input was emphasized by Krashen. At the same time, many studies have highlighted the linguistic, informational, and pedagogical purpose of documentary film in language skill learning. The base of the studies is the cognitive theory of multimedia learning. Accordingly, the present study has two main objectives, firstly to highlight the importance of using documentary film in enhancing the learning of Arabic as a second language (ASL) writing skill. Secondly, to analyse and discuss local experts’ views on the utilization of documentary film in the ASL classroom. For this purpose, a questionnaire was distributed among 12 experts in the field of ASL in Malaysian public universities. Their responses were collected and analysed based on closed-ended and open-ended surveys. The findings and discussion indicated that strong recommendations are given to the credit of the research question. The ASL experts recommend types of documentary films to be utilized, the category of writing skill that can be developed and the appropriate instruction technique to be used in the classroom.